Economic Doctrines of Islam - lmtiazuddin Ahmad (International Institute of Islamic Thought, 1997)
Dr. Haq’s book belongs to the same group of issue-oriented studies in Islamic economics that Umar Chapra’s’ books do. However, unlike Chapra, who first provides a critical evaluation of the failed modem economic systems and then establishes the supremacy of Islam’s economic development strategy, Irfan Ul Haq starts out with a comprehensive expository analysis of Islamic mnomic doctrines. He then relies on extensive personal interpretation to derive and then justify various policy prescriptions for the promotion of economic growth in an Islamic economy. The book contains four parts, which are divided into fourteen chapters. The first five chapters in the first two parts discuss Islamic methodology and Islam’s social and political order. The book‘s major theme is included in the third and fourth parts where the author discusses most of the economic issues and policies. Since the controversial policy-oriented economic subjects are covered in these parts, I will concentrate on the evaluation of these major economic subjects. These subjects include the proper role of the public sector, fard al-kifayah and its implications, interest-free financing, land ownership and tenure, taxation, poverty, employment, and the policies to provide economic essentials. Fard al-Kifayah and Its Implications for Economic Policy In discussing the principle of fard al-kifayah and the role of the Islamic state in providing public goods, Dr. Haq advocates a policy of nationalization of resources as an appropriate policy for an Islamic state to follow. The same policy is extended elsewhere to include price fixing and direct control of the grain trade, and by implication, of all other commercial activity. Rather than providing a justification for such a policy on economic and Islamic grounds, he carries out his entire discussion on the assumption that big government has the capacity and the means to solve all economic problems. This thesis, in my view, contradicts the basic economic philosophy of Islam, which incorporates private initiative and free enterprise with a primary focus on the individual as a decision maker and khurifah of God on earth. The author continues to overlook the fact that equity and efficiency are not complementruy, but often competitive. An over-emphasis on the distributional justice of Islam creates an erroneous impression that in the Islamic worldview, economic growth and development are relegated to a secondary role. This is not only incorrect, but it also contradicts the very thesis of his book. Elsewhere I have elaborated on the Qur’anic view of man and its implications for his economic role. land Ownership and Tenure In the beginning of chapter 10, the author correctly notes that Islam allows land accumulation without any restrictions and recommends a balanced ...